Dive Risk Factors, Gas Bubble Formation, and Decompression Illness in Recreational SCUBA Diving: Analysis of DAN Europe DSL Data Base - Cialoni, Danilo; Pieri, Massimo; Balestra, Costantino; Marroni, Alessandro (Frontiers in Psychology, 2017)
Introduction: The popularity of SCUBA diving is steadily increasing together with the number of dives and correlated diseases per year. The rules that govern correct decompression procedures are considered well known even if the majority of Decompression Sickness (DCS) cases are considered unexpected confirming a bias in the “mathematical ability” to predict DCS by the current algorithms. Furthermore, little is still known about diving risk factors and any individual predisposition to DCS. This study provides an in-depth epidemiological analysis of the diving community, to include additional risk factors correlated with the development of circulating bubbles and DCS. Materials and Methods: An originally developed database (DAN DB) including specific questionnaires for data collection allowed the statistical analysis of 39099 electronically recorded open circuit dives made by 2629 European divers (2189 males 83.3%, 440 females 16.7%) over five years. The same dive parameters and risk factors were investigated also in 970 out of the 39099 collected dives investigated for bubble formation, by 1-minute precordial Doppler, and in 320 sea-level dives followed by DCS symptoms. Results: Mean depth and GF High of all the recorded dives were 27.1 m, and 0.66 respectively; the average ascent speed was lower than the currently recommended “safe” one (9-10 m/min). We found statistically significant relationships between higher bubble grades and BMI, fat mass, age and diving exposure. Regarding incidence of DCS, we identified additional non-bubble related risk factors, which appear significantly related to a higher DCS incidence, namely: gender, strong current, heavy exercise and workload during diving. We found that the majority of the recorded DCS cases were not predicted by the adopted decompression algorithm and would have therefore been defined as “undeserved”. Conclusion: The DAN DB analysis shows that most dives were made in a “safe zone”, even if data show an evident “grey area” in the “mathematical” ability to predict DCS by the current algorithms Some other risk factors seem to influence the possibility to develop DCS, irrespective of their effect on bubble formation, thus suggesting the existence of some factors influencing or enhancing the effects of bubbles.